Measurements of atmospheric aerosol hygroscopic growth based on multi-channel Raman-Mie lidar - Zhao, Yuefeng; Wang, Xu; Cai, Yangjian; Pan, Jie; Yue, Weiwei; Xu, Huaqiang; Wang, Jingjng (Atmospheric environment (1994), 2021)
In this study, an effective method with a multi-channel Raman-Mie lidar has been proposed to detect the hygroscopic growth of atmospheric aerosol in the boundary layer, and the effect of aerosol hygroscopic growth on the optical and microphysical properties of aerosol particles is studied. The vertical relative humidity profile is obtained by combining calibrated water vapor mixing ratio and temperature profiles from Raman-Mie lidar. Two cases were selected in Hefei to analyze the aerosol hygroscopic growth. Case studies show that the increase of the backscatter coefficient of aerosol is consistent with the increase of relative humidity, and the decrease of Ångstrom exponent indicates the increasing aerosol particle size due to the hygroscopic growth process. The Kasten model is used to fit the aerosol hygroscopic enhancement factor, and the b value from the Kasten parameterization for Case II is much larger than that for Case I, which shows the stronger hygroscopicity in Case II. The results indicate that the multi-channel Raman-Mie lidar has potential in the measurements of the hygroscopic growth of aerosols. •Acquiring relative humidity vertical profile exclusively from Raman- Mie lidar data.•The lidar-based results were compared with in situ measurements.•Air quality was explained with aerosol hygroscopicity.•Verified the feasibility of Raman-Mie lidar in studying aerosol hygroscopic growth.•Providing an effective method for studying the aerosol hygroscopic growth.